Poly(Sarcosine) Surface Modification Imparts Stealth‐Like Properties to Liposomes. Issue 50 (13th November 2019) - Bleher, Stefan; Buck, Jonas; Muhl, Christian; Sieber, Sandro; Barnert, Sabine; Witzigmann, Dominik; Huwyler, Jörg; Barz, Matthias; Süss, Regine
Abstract: Circulation lifetime is a crucial parameter for a successful therapy with nanoparticles. Reduction and alteration of opsonization profiles by surface modification of nanoparticles is the main strategy to achieve this objective. In clinical settings, PEGylation is the most relevant strategy to enhance blood circulation, yet it has drawbacks, including hypersensitivity reactions in some patients treated with PEGylated nanoparticles, which fuel the search for alternative strategies. In this work, lipopolysarcosine derivatives (BA‐pSar, bisalkyl polysarcosine) with precise chain lengths and low polydispersity indices are synthesized, characterized, and incorporated into the bilayer of preformed liposomes via a post insertion technique. Successful incorporation of BA‐pSar can be realized in a clinically relevant liposomal formulation. Furthermore, BA‐pSar provides excellent surface charge shielding potential for charged liposomes and renders their surface neutral. Pharmacokinetic investigations in a zebrafish model show enhanced circulation properties and reduction in macrophage recognition, matching the behavior of PEGylated liposomes. Moreover, complement activation, which is a key factor in hypersensitivity reactions caused by PEGylated liposomes, can be reduced by modifying the surface of liposomes with an acetylated BA‐pSar derivative. Hence, this study presents an alternative surface modification strategy with similar benefits as the established PEGylation of nanoparticles, but with the potential of reducing its drawbacks. Abstract : Amphiphilic pSar derivatives are synthesized and incorporated into the bilayer of liposomes to impart stealth‐like properties. Formulations show similar characteristics as PEGylated liposomes regarding their surface charge shielding potential and reduced clearance by macrophages in zebrafish. Liposomes modified with an acetylated pSar derivative show lower complement activation levels compared to those observed for PEGylated liposomes.